Comparison of methodologies of CSR index: application to the PSI 20 companies - Fernandes, Paula Odete (2013)
Corporate Social Responsibility (CSR) has assumed increasing importance over the past several decades, globally resulting from companies’ response to the demands of markets and society for responsible growth, both social and environmentally. At a European level, the CSR was initially boosted in 1993 by the former President of the European Commission, Jacques Delors, who called for more socially responsible action from companies, and culminated in 2001 with the publication of the Green Paper on CSR, by the European Commission in which the areas and guidelines for desirable social responsibility practices were defined. The measurement of social or CSR performance has not been consensual, which accounts for the existence of several methods. These use a variety of criteria ranging from expert evaluation to the analysis of reports and other documents or considerations of performance measures of pollution control. Each of these criteria is not exempt from criticism and limitations, as they are one-dimensional or do not reflect all aspects of CSR. Based on these measures, some evaluation CSR indices were developed, having been used in decision-making and positioning of the companies in their social and environmental performance. The most commonly used indices are those provided by the rating agency Kinder, Lindenberg and Domini index or reputation index of Fortune. This paper aims to compare the application of two methods in defining the levels of CSR from a CSR index, constructed for 19 of the 20 companies comprising the PSI-20, the Portuguese stock market index, the Euronext Lisbon. One of the methodologies defines five intervals of CSR using the cut-point method; the other considers a scale of 5 points (5 grades) with constant intervals. In order to construct the index, 247 items were considered, comprising the different dimensions of social responsibility suggested by the European Commission Green Paper on CRS of 2001 and the guidelines of the Global Reporting Initiative. We analyzed the contents of sustainability reports and financial reports of companies under research in order to assign a score (which will be 0 if the item is not observed, 0.5 if is only partially observed or 1 whether it is observed) for measurement of each item of responsibility, since there are no quantifiable and objective social responsibility indicators. The CSR index of a company, at any given time, is the sum of the scores across all 247 items. The categorization of companies in the CSR levels depends on the referred methodology to the definition of intervals. In brief, by using the two approaches, we found that the Portuguese companies which were analyzed denote a growing sensitivity in the adhesion and dissemination of their social responsibility practices, investing in a more specific and detailed disclosure and, in particular, complying with the guidelines of the Global Reporting Initiative.